New user? Sign up

Existing user? Sign in

C1 : x2 y2 - 2ax + c = 0 lies completely inside C2 : x2 y2 - 2bx + c = 0 ; (a not equals b), then prove that ab>c>0

Note by Gopal Chpidhary 3 years, 10 months ago

Sort by:

I would like to clarify but the equations stated doesn't look like the equations for a circle.

Log in to reply

that's x^2 + y^2 -2ax +c = 0 and x^2 + y^2-2bx+c=0..........try with this

Also, ab > c > 0 is to be proven?

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestI would like to clarify but the equations stated doesn't look like the equations for a circle.

Log in to reply

that's x^2 + y^2 -2ax +c = 0 and x^2 + y^2-2bx+c=0..........try with this

Log in to reply

Also, ab > c > 0 is to be proven?

Log in to reply